Investigation of Classroom Applications for Multicultural Education in Terms of Various Variables - Soner YILDIRIM; Münevver MUYO YILDIRIM (Prizren Social Science Journal, 2019)
In this study, it was examined whether the teachers' in-class practices towards multicultural education in Kosovo differ according to gender, professional seniority, mother tongue, level and branch variables. Descriptive screening model was used in the study. The study group consisted of 975 Turkish, Albanian and Bosnian teachers working in the provinces of Prizren, Pristina, Mamusha, Reçane and Restelitsa in the 2016-2017 academic year. The education In-Class Practices Scale m developed by the researcher as a data collection tool to determine the classroom practices of teachers for multicultural educational practices was applied in this study. The results of the study showed that some variables differed significantly on classroom teaching practices. These are the mother tongue, the level, and the branch variables. On the other hand, it was determined that gender and professional seniority variables did not cause a significant difference in classroom practices.